2002
DOI: 10.1080/1071576021000005249
|View full text |Cite
|
Sign up to set email alerts
|

Activin, a Grape Seed-derived Proanthocyanidin Extract, Reduces Plasma Levels of Oxidative Stress and Adhesion Molecules (ICAM-1, VCAM-1 and E-selectin) in Systemic Sclerosis

Abstract: This study evaluated whether a new generation antioxidant Activin derived from the grape seed proanthocyanidins, could reduce the induction of the adhesion molecules as a result of inflammatory response in the plasma of systemic sclerosis (SSc) patients. SSc patients were divided into two groups: one group was treated with Activin, a grape seed-derived proanthocyanidins, while the other group served as control. Patients were given Activin 100 mg/day orally for one month after which the blood samples were withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 23 publications
3
50
0
1
Order By: Relevance
“…This implies a possible benefit of antioxidant treatment. In scleroderma, however, only a few studies have been undertaken in this respect so far, and they yielded inconsistent outcomes (Denton et al 1999;Herrick et al 2000;Kalin et al 2002). The difficulty in assessing the benefit of antioxidant treatment lies probably in the subjectivity or insensitivity to change of most of the measures currently in use (Herrick & Matucci Cerinic 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This implies a possible benefit of antioxidant treatment. In scleroderma, however, only a few studies have been undertaken in this respect so far, and they yielded inconsistent outcomes (Denton et al 1999;Herrick et al 2000;Kalin et al 2002). The difficulty in assessing the benefit of antioxidant treatment lies probably in the subjectivity or insensitivity to change of most of the measures currently in use (Herrick & Matucci Cerinic 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, Kalfin et al demonstrated that proanthocyanidin from grapeseeds reduced the level of ICAM-1 in the sclerosis patient. 43) The NF-κB transcription factor is constitutively activated in many types of cancer including in breast cancer cells. The NF-κB signaling pathway is known to regulate the expression of various genes involved in the process of tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Since GSPE also contain high amount (84%) of proanthocyanidins, antioxidant activities of proanthocyanidins might contribute to the antinociceptive effect of GSPE. In fact, this notion is supported also by the observation that Croton celtidifolius extract containing high amount of proanthocyanidins (75%) exhibited antinociceptive effect in the formalin test.…”
Section: Discussionmentioning
confidence: 99%